Realising the potential of Q methodology in nursing research - Lim, Eric; Wynaden, Dianne; Baughman, Frank; Heslop, Karen (Elsevier, 2020)
Background Mixed methods research designs are becoming increasingly popular in nursing to explore complex clinical issues and to generate knowledge useful to improve the quality of nursing practice and clients’ health outcomes. Q methodology is one such research design that combines the strengths of both qualitative and quantitative approaches to examine scientifically peoples’ subjectivity towards a subject area. Aim This paper aims to provide an introduction to Q methodology and outlines the steps taken when conducting research on clinical issues. Methods A clinical example of nurses caring for clients with a risk for aggression is used to illustrate how Q methodology was used to examine this subject area. The five sequential phases of Q-methodology integrate both approaches in a continuous interaction in a single study design, enabling researchers to explore the breadth and depth of factors that influence participants’ responses towards the topic under investigation. Findings Q methodology is a unique mixed methods design as it does not require the researcher to spend time triangulating two or more research approaches into one single study or to conduct a qualitative and a quantitative study separately. The unique characteristics of Q methodology can be advantageous for nurses who have complex clinical workloads but also want to conduct research. Moreover, Q methodology does not require a large sample size, hence it is resource- and cost-effective. Discussion Q methodology allows both nurse clinicians and nurse academics to explore new dimensions of staff and clients’ subjectivity which is important for the development of evidence based practice. Conclusion Adding Q methodology to the nursing research repertoire can facilitate nurse researchers to expand clinical research opportunities, to improve client care and to build capacity in early career nurse researchers.